Diagnostic value of VIA comparing with conventional pap smear in the detection of colposcopic biopsy proved CIN - Hegde, D; Shetty, H; Shetty, PK; Rai, S; Manjeera, L; Vyas, N; Hegde, A; Mallya, H; Rajesh, A (Health Renaissance, 2011)
Introduction: Cervical cancer, the leading malignancy among Indian women is preventable and curable if detected at an early stage using proper screening tools. We conducted a study to assess the role of visual inspection with acetic acid as an alternative to pap smear and in screening program for cervical cancer in low resource settings. Methods: Two hundred and twenty five women in reproductive age group attending the Gynecology department at K.S Hegde Charitable Hospital were enrolled in the study. A Papanicolaou smear and visual inspection of the cervix with acetic acid was done. All women then underwent colposcopy using the videocolposcope. All patients who tested positive on screening then underwent colposcopy guided biopsy. Pap smear of low grade squamous intraepithelial lesion (LSIL) and above was taken as abnormal. The statistical test used was chi square test and results were computed using SPSS version 12.0. Results: Out of 225 patients, VIA was positive in 27(12%) patients and pap smear was abnormal in 26(11.7%). There were 15 LSIL, 6 high grade squamous intraepithelial lesion (HSIL) and 5 were squamous cell carcinoma. On biopsy, there were 15 mild dysplasia, 2 moderate dysplasia, 4 severe dysplasia and 3 squamous cancers. Pap smear had a sensitivity of 83%, specificity of 98%, positive predictive value of 80 % and negative predictive value of 97.9%. VIA had a sensitivity of 70.8%, specificity of 95%, and positive predictive value of 62.9 % and negative predictive value of 96.5%. Conclusion : Since diagnostic values of VIA is comparable to pap smear, and it performs well in detecting high grade lesion we conclude that VIA can be used as a screening modality for cervical cancer in low resource settings. Keywords: visual inspection with acetic acid; pap smear- colposcopy; cervical cancer; low resource settings DOI: http://dx.doi.org/10.3126/hren.v9i3.5579 HR 2011; 9(3): 134-139